Uveitis as a potential predictor of acute myocardial infarction in patients with Behcet's disease: a population-based cohort study. Issue 1 (15th January 2021) - Chen, Yu-Yen; Lai, Yun-Ju; Yen, Yung-Feng; Chen, Hsin-Hua; Chou, Pesus
Abstract : Objectives: To investigate whether uveitis is a predictor of acute myocardial infarction (AMI) among patients with Behcet's disease (BD). Design: Retrospective cohort study. Setting: Patients with BD were retrieved from the whole population of the Taiwan National Health Insurance Research Database from 1 January 2001 to 31 December 2013. Participants: Among the 6508 patients with BD, 2517 (38.7%) were in the uveitis group and 3991 were in the non-uveitis group. Primary and secondary outcome measures: Kaplan-Meier curves were generated to compare the cumulative hazard of AMI in the uveitis and non-uveitis groups. Multivariate Cox regression analysis was used to estimate the adjusted HRs and 95% CI of AMI, and was adjusted for age, gender, systemic comorbidities (eg, hypertension, diabetes, hyperlipidaemia, smoking) and clinical manifestation of BD (eg, oral ulcers, genital ulcers, skin lesions, arthritis and gastrointestinal involvement). Results: The mean age of the BD cohort was 38.1±15.1 years. Compared with non-uveitis patients, uveitis patients were significantly younger and male predominant. There was no significant difference between the two groups for most proportions of systemic comorbidities and clinical manifestations. The Kaplan-Meier method with the log-rank test showed that the uveitis group had a significantly higher cumulative hazard for patients with AMI compared with the non-uveitis group (p<0.0001). In the multivariable Cox regression after adjustment for confounding factors, patients with uveitis had a significantly higher risk of AMI (adjusted HR 1.87; 95% CI 1.52 to 2.29). Other significant risk factors for AMI were age, hypertension, smoking, and skin lesions. Conclusions: Statistical analyses from the nationwide database demonstrated that uveitis is a potential predictor of AMI in patients with BD.